2017
DOI: 10.4274/tjo.87300
|View full text |Cite
|
Sign up to set email alerts
|

Selective Laser Trabeculoplasty vs. Fixed Combinations with Timolol in Practice: A Replacement Study in Primary Open Angle Glaucoma

Abstract: Objectives:To evaluate the potential of selective laser trabeculoplasty (SLT) in two arms (360˚ vs. 180˚) as a replacement for fixed combinations (FCs) with timolol in primary open angle glaucoma over 6 months.Materials and Methods:Of 40 patients in a prospective, comparative, interventional case series, 18 eyes and 22 eyes were randomized to SLT 180º and SLT 360º groups, respectively, along with 40 fellow-control eyes. FC with timolol was discontinued on the day of treatment for the eye to be operated on, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Associations between energy level and IOP reduction were not examined in that study. 69 In contrast to Ozen and colleagues and Tufan and colleagues, Tawfique and colleagues compared the results of 90-degree and 360-degree SLT in 67 patients with OAG or OHT. In that study IOP reductions were not examined, but treatment survival extents between the 2 groups were reported.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Associations between energy level and IOP reduction were not examined in that study. 69 In contrast to Ozen and colleagues and Tufan and colleagues, Tawfique and colleagues compared the results of 90-degree and 360-degree SLT in 67 patients with OAG or OHT. In that study IOP reductions were not examined, but treatment survival extents between the 2 groups were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Across all of the studies summarized in Table 5 , four reported on the energy range used for treatment, which varied between 0.2 and 1.4 mJ per treatment spot. 11 , 68 , 69 , 70 The mean total energy was reported in two studies as 73.6 and 90.2 mJ. 50 , 71 Another study compared the effectiveness of SLT at 90, 180 or 360 degrees to that of topical treatment, 58 while in the other seven studies the energy was applied to 360 degrees of the TM.…”
Section: Slt Dose Response Versus Topical Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty fellow eyes made up the control group. At the 6-month follow-up, the study showed no statistically significant differences between groups ( p < 0.001) [ 41 ].…”
Section: Efficacy Of Treatmentmentioning
confidence: 99%